Impact of Brain-Based Teaching on the Conceptual Understanding of Newton's Laws of Motion - Comillo, Rosendo III; Voltaire M. Mistades (Universitas Negeri Semarang, 2025)
Grounded in cognitive neuroscience, Brain-Based Teaching (BBT) enhances science instruction by aligning classroom practices with how the brain optimally learns and processes information. This mixed-methods study investigated the effectiveness of BBT in improving Grade 8 students' conceptual understanding of Newton's Laws of Motion. Conducted in a public school in Manila, Philippines, the study involved 51 students who participated in an intervention utilizing BBT strategies, including relaxed alertness, orchestrated immersion, and active processing. Quantitative data were collected through a validated 25-item concept test, daily performance worksheets, and a Student Perception of Instruction Questionnaire (SPIQ). Qualitative data came from student journals and semi-structured interviews. Findings showed a significant improvement in post-test scores (M = 9.35), as confirmed by a paired-sample t-test (t(50) = 3.80, p < .001) and a moderate effect size (Cohen's d = 0.67). Daily worksheets consistently received